Pro‐tumorigenic Effects of Transforming Growth Factor Beta 1 in Canine Osteosarcoma. (31st March 2014) - Portela, R.F.; Fadl‐Alla, B.A.; Pondenis, H.C.; Byrum, M.L.; Garrett, L.D.; Wycislo, K.L.; Borst, L.B.; Fan, T.M.
<x xml:space="preserve">Abstract</x> Background Transforming growth factor beta 1 (TGFβ1) is a pleiotropic cytokine that contributes to reparative skeletal remodeling by inducing osteoblast proliferation, migration, and angiogenesis. Organic bone matrix is the largest bodily reservoir for latent TGFβ1, and active osteoblasts express cognate receptors for TGFβ1 (TGFβRI and TGFβRII). During malignant osteolysis, TGFβ1 is liberated from eroded bone matrix and promotes local progression of osteotropic solid tumors by its mitogenic and prosurvival activities. Hypothesis Canine osteosarcoma (OS) cells will possess TGFβ1 signaling machinery. Blockade of TGFβ1 signaling will attenuate pro‐tumorigenic activities in OS cells. Naturally occurring primary OS samples will express cognate TGFβ1 receptors; and in dogs with OS, focal malignant osteolysis will contribute to circulating TGFβ1 concentrations. Animals Thirty‐three dogs with appendicular OS. Methods Expression of TGFβ1 and its cognate receptors, as well as the biologic effects of TGFβ1 blockade, was characterized in OS cells. Ten spontaneous OS samples were characterized for TGFβRI/II expressions by immunohistochemistry. In 33 dogs with OS, plasma TGFβ1 concentrations were quantified and correlated with bone resorption. Results Canine OS cells secrete TGFβ1, express cognate receptors, and TGFβ1 signaling blockade decreases proliferation, migration, and vascular endothelial growth factor secretion. Naturally occurring OS samples abundantly and uniformly express TGFβRI/II, and in OS‐bearing dogs, circulating TGFβ1 concentrations correlate with urine N‐telopeptide excretion. Conclusions and Clinical Importance Canine OS cells possess TGFβ1 signaling machinery, potentially allowing for the establishment of an autocrine and paracrine pro‐tumorigenic signaling loop. As such, TGFβ1 inhibitors might impede localized OS progression in dogs.